FİRDAWSİ, SHAH-NAMAH, WRITING OF SHAH-NAMAH AND FİRDEVSÎ ARTICLE IN MEŞÂHÎR-İ İSLÂM - Hasan GÜLTEKİN (Fırat University, 2019)
Persian Literature have influence on the Ottoman Classical Turkish Literature in the 15th and 16th century. These influences usually appear on the literary works. Shah-namah’s influences that was written by Firdawsi are especially attract attention. One of very important official work of states are historiography. Interpretations of Shah-namah are great number and variety of the languages. Interpretations of Shah-namah are both prose style and written in verse. In addition to these, autocephalous shah-namah was written by different writers. The purpose of taking the Shah-namah as a source and example for classical literature, given the extraordinary qualities of masnavi heroes by Firdawsi are used as a tool to make a comparison between the superiority of Divan poet vaunted by the person. At the end of this article we added Firdevsî article that is at the Vehbî 's Meşâhîr-i İslâm that we have made a transcription of the article that contains some information on the different knowledge about Firdawsi and Shah-namah. Some of the information in our transcription we provide some information in contradicts the Persian literature sources as well. The most remarkable thing of this information is: The reason for writing the Shah-namah, according to Hussein Feriver: Sultan Mahmud has established that a Turkish state that Firdevsi didn't accept this event but contrary to what Feriver is that it is noted in the Firdevsî article that Sultan Mahmud wanted to write a shah-namah from the Firdawsi. Similarly, given as h. 329 by Feriver Firdawsi’s date of birth, that the Firdevsî article was written as h. 323. Additionally, Zebihullah Safa said that Firdawsi had written the Shah-namah before he met Sultan Mahmud. With this information contradicts the information in Firdevsî article and the claims of Feriver.